MINDFUL HAPPINESS NOWADAYS: - B Lemmelijn (Acta Theologica, 2018)
Our current times are characterized by a strange paradox. The secularized world we live in no longer embraces Christianity as such nor its concrete praxis in churches. Simultaneously, however, our times are very remarkably searching for the things that “do really matter”, for “happiness”, “meaning” and “wisdom”. This occurs in a real plethora of different ways and against the background of distinct traditions. Nevertheless, many of the intrinsic beautiful elements in this plethora of contemporary approaches simply are and have for ages been as much Judeo-Christian thinking and living. Indeed, we discern them in the monastic tradition, in medieval mysticism, in the (re-)new(ed) tendencies of Christian meditation, in the Biblical texts, and especially in Biblical Wisdom Literature. All too often, however, they have been forgotten beneath the dust of times. We should rediscover them and situate them in this new and actual context.